2016
DOI: 10.18520/cs/v111/i9/1524-1531
|View full text |Cite
|
Sign up to set email alerts
|

Importance and Sensitivity of Variables Defining Throw and Flyrock in Surface Blasting by Artificial Neural Network Method

Abstract: Rock breakage by explosives is followed by throw or heaving the broken material and occasional flyrock. Heaving is a desired feature of blasting for efficient mucking. However, flyrock is a rock fragment that travels beyond the designated distance from a blast in surface mines, and poses a threat to adjacent habitats. Here, we decipher the importance and sensitivity of the variables and factors used to establish the predictive regime of throw with more emphasis on flyrock. The data collected were modelled usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 0 publications
0
16
0
2
Order By: Relevance
“…Armaghani et al (2016a) No discussion on testing methodology. Raina and Murthy (2016) Blast data were collected from mines, however, there was no specific discussion on type of data or data acquisition methodology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Armaghani et al (2016a) No discussion on testing methodology. Raina and Murthy (2016) Blast data were collected from mines, however, there was no specific discussion on type of data or data acquisition methodology.…”
Section: Discussionmentioning
confidence: 99%
“…The testing methodology applied by researchers now becomes critical in order to determine what these error(s) are and the magnitude(s) thereof. Monjezi, Amini Khoshalan, and Yazdian Varjani (2010) 9-16-2 Monjezi et al (2012) 9-5-2-1 Raina,Murthy, and Soni (2013) 7-20-14-8-1 Ghasemi (2014) 6-9-1 Raina and Murthy (2016) 20-16-6-4-1…”
Section: Ai Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial intelligence (AI) has been increasingly applied in the form of artificial neural networks (ANNs) and fuzzy logic (Tivedi et al, 2014). Such routines have been used with up to 21 parameters describing the blast and to some degree, the properties of the rock mass to be blasted (Raina and Murthy, 2016b). The independent parameters may be combined in linear arrays, or raised to various powers, or included in various mathematical functions such as logarithms and exponentials.…”
Section: Historical Correlation Studiesmentioning
confidence: 99%
“…Raina A.K. et al [33][34][35] launched a series of studies on the fly-rock problem in throwing blasting. Aiming at the difficulty in throwing rock fragments from traditional cut blasting, Zhang H et al [36] proposed and demonstrated an advanced blasting technology.…”
Section: Introductionmentioning
confidence: 99%